2013
DOI: 10.1002/elps.201200686
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rhinovirus subviral A particles via capillary electrophoresis, electron microscopy and gas phase electrophoretic mobility molecular analysis: Part II

Abstract: Human rhinoviruses (HRVs) are valuable tools in the investigation of early viral infection steps due to their far reaching (although still incomplete) characterization. During endocytosis, native virions first loose one of the four capsid proteins (VP4); corresponding particles sediment at 135S and were termed subviral A particles. Subsequently, the viral RNA genome leaves the viral shell giving rise to empty capsids. In continuation of our previous work with HRV serotype 2 (HRV2) intermediate subviral particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This stretch corresponds to roughly 10% of the total RNA, a number similar to an earlier estimate of ca. 7%, based on the UV absorbance ratios at 200 and 260 nm of the peaks of native virus and RNase-treated intermediate-particles in capillary electrophoresis (51).…”
Section: Discussionmentioning
confidence: 99%
“…This stretch corresponds to roughly 10% of the total RNA, a number similar to an earlier estimate of ca. 7%, based on the UV absorbance ratios at 200 and 260 nm of the peaks of native virus and RNase-treated intermediate-particles in capillary electrophoresis (51).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of divalent cations (e.g. Mg 2+ ) known to stabilize the MB stem was omitted as these had been found to stabilize viral uncoating intermediates [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, the alteration of HRV-A2 can either be triggered by acidification (pH ≤5.8), which mimics the in vivo situation in endosomes, or by heating (≥10 min to ≥56 °C) [ 7 ]. Depending on the concentration of divalent cations, subviral A particles or empty viral capsids are formed [ 8 , 9 ]. Several orthogonal analytical methods like sucrose density centrifugation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the surfactant SDS as BGE additive allows to overcome the common troubles of irreproducibility encountered in the CZE analyses of non‐enveloped icosahedral viruses . Although BGE additives may not be necessary in some cases , when the presence of SDS is required, it becomes problematic to understand the behavior of non‐enveloped icosahedral viruses since the way by which SDS interacts with the surface of such viruses is poorly known.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, non‐enveloped icosahedral viruses possess a global negative surface charge at pH higher than the isoelectric point contributing to proffer them an electrophoretic mobility . Exploiting this characteristic, it has been shown that capillary zone electrophoresis (CZE), a separative analytical technique based on the difference of the electrophoretic mobility of the analytes , can be applied in the separation, detection and quantification of viral, subviral and virus‐like particles in aqueous media . However, in practice, the CZE analysis of viruses is harder than of molecules, where uncontrolled viral particles aggregation and capillary wall adsorption responsible of irreproducible results having been often encountered .…”
Section: Introductionmentioning
confidence: 99%